FinTech and financial inclusion: the mediating role of digital marketing - Al-Slehat, Zaher Abdel Fattah (Business: Theory and Practice, 2023)
This study aims to test the role of digital marketing as a mediating variable in the relationship between financial technology and financial inclusion. The researcher applied the descriptive analytical approach to the data collected by developing a questionnaire distributed to 375 employees in the Jordanian banking sector. The researcher also used structural equation modeling to test the study hypotheses through SmartPLS software 3. One of the study’s most important findings is that digital marketing partially mediates the relationship between financial technology and financial inclusion. The study recommends that the Jordanian commercial banking sector should use advanced strategies that enhance technological innovation and digital marketing through the existence of an evolved environment for financial technology that is optimally exploited.